Comparison of the Virulence of Pathogenic Newcastle Disease Viruses Belonging to the Same or Different Genotypes - Merino, Ruben; Villegas, Hilda; Quintana, Jose A.; Calderon, Norma (International Journal of Poultry Science, 2011)
Virulent Newcastle disease has threatened the Mexican poultry industry since 1946. Two Mexican virulent strains belonging to the Chimalhuacan (Quail2006) and Torreon (Chicken2000) lineages of genetic group V, as well as the ancient Mexican strain named Queretaro and a Beaudette C-like US strain (genotype II) were tested by pathogenesis analysis in commercial 5 weeks old broiler chickens, comparing the lesions severity on primary and secondary lymphoid organs after 24, 36, 48, 60, 72, 84 and 96 h postinoculation (hpi). Organ samples were analyzed by light and electron microscope and by virus isolation. The Quail2006 isolate caused more severe clinical signs and microscopic lesions (p<0.05) in bursa of Fabricius, thymus, spleen and bone marrow of 5 weeks old broiler chickens. Ultra-structural changes were seen as early as 24 hpi and the highest lesion score in different organs was reached between 72 and 96 hpi in some cases. Ultra-structural observation and virus isolation confirmed the virus presence in all evaluated organs. Quail2006 strain was more virulent than Chicken2000, tough they belong to the same genotype and is also more virulent than Queretaro and Beaudette C-like strains (genotype II). The virus effect on lymphoid organs enhances its importance in countries where vaccinated commercial poultry is protected against the death, but not against infection or virus replication in lymphoid organs, which can lead to reduced productivity and susceptibility to other infections. Full characterization of NDV should include virulence tests in susceptible animals, besides the standard indices and sequence analysis.